2018
DOI: 10.1177/0194599818792191
|View full text |Cite
|
Sign up to set email alerts
|

Upper Airway Stimulation in Patients Who Have Undergone Unsuccessful Prior Palate Surgery: An Initial Evaluation

Abstract: Upper airway stimulation therapy (UAS) is a new option for treatment of obstructive sleep apnea (OSA) in patients unable to tolerate continuous positive airway pressure (CPAP). We set out to evaluate the effectiveness of UAS in patients who have undergone prior palate surgery. We designed a retrospective review and evaluated patients undergoing UAS at 2 academic centers. We recorded demographic and pre- and postoperative polysomnogram (PSG) data. We compared the cohort of patients who had undergone prior palat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

5
5

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 9 publications
1
11
0
1
Order By: Relevance
“…21 Additionally, no differences in outcomes have been identified between elderly (> 65 years) and nonelderly (< 65 years) cohorts, as well as those with and without prior palatal surgery. 22,23 Values represent mean reduction (preoperative value − postoperative value) ± standard deviation, unless otherwise stated. Definition 1 = AHI reduction > 50% + AHI < 20 events/h.…”
Section: Discussionmentioning
confidence: 99%
“…21 Additionally, no differences in outcomes have been identified between elderly (> 65 years) and nonelderly (< 65 years) cohorts, as well as those with and without prior palatal surgery. 22,23 Values represent mean reduction (preoperative value − postoperative value) ± standard deviation, unless otherwise stated. Definition 1 = AHI reduction > 50% + AHI < 20 events/h.…”
Section: Discussionmentioning
confidence: 99%
“…52 A retrospective study showed that prior palatal surgery do not influence HNS clinical outcome. 53,54 Another retrospective analysis found no indication for patients to routinely undergo UPPP before HNS, while palatal surgery could be suggested in case of non-adequate response to HNS after the implantation. 55 Accordingly, a recent study based on the Adhere Registry data (n = 299) showed that previous surgery is not associated with HNS outcomes.…”
Section: Patient Selection and Efficacy Predictorsmentioning
confidence: 99%
“…In therapy responders, HNS with respiratory sensing can normalize sleep-related quality of life with very good patient satisfaction [27,28]. Patient age and previous upper airway surgery appear not to affect effectiveness [29,30]. Several retrospective comparative studies show better OSA outcomes of HNS treatment compared to traditional sleep surgery [31][32][33].…”
Section: Overview Of Evidencementioning
confidence: 99%